Risk factors for infection development after transrectal prostate biopsy and the role of resistant bacteria in colonic flora - Emine Dilek Eruz; Aysun Yalci; Eriz Ozden; Halide Aslaner; Suna Ogucu-Durgun; Deniz Derya Koseoglu-Taymur; Kemal Osman Memikoglu; Hakan Erdem; Halil Kurt (Journal of Infection in Developing Countries)
Introduction: In this study, we aimed to identify risk factors for the development of infectious complications after prostate biopsy and to investigate the role of intestinal colonization of bacteria that are resistant to prophylactic antibiotics.